2007
DOI: 10.1021/jp0713920
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Water on the Dispersion of Vanadia Supported on Silica SBA-15:  A Combined XPS and Raman Study

Abstract: The influence of water on the dispersion and structure of silica SBA-15-supported vanadia model catalysts has been studied using X-ray photoelectron spectroscopy (XPS) and Raman spectroscopy, which were combined within one experimental setup, as well as UV-vis diffuse reflectance spectroscopy. By performing timedependent XPS experiments, the influence of UHV/X-ray radiation could be eliminated by extrapolation of the observed temporal changes to t ) 0. XPS characterization reveals that the V2p 3/2 emission con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
105
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(122 citation statements)
references
References 39 publications
17
105
0
Order By: Relevance
“…The XPS peaks at 517.5 eV and 516.4 eV can readily be assigned to V 5+ and V 4+ species since the absolute BE, and in particular the BE difference of ΔE = 1.1 eV, agrees reasonably well with literature [27]. The peak centered at 518.7 eV is characteristic for highly dispersed V 5+ species as discussed in detail in Hess et al [19]. It can be concluded a loss of 3-dimensional character of the surface vanadium oxide species, i.e.…”
Section: In Situ Nexafs and Xps Of Vxoy/sba-15supporting
confidence: 77%
“…The XPS peaks at 517.5 eV and 516.4 eV can readily be assigned to V 5+ and V 4+ species since the absolute BE, and in particular the BE difference of ΔE = 1.1 eV, agrees reasonably well with literature [27]. The peak centered at 518.7 eV is characteristic for highly dispersed V 5+ species as discussed in detail in Hess et al [19]. It can be concluded a loss of 3-dimensional character of the surface vanadium oxide species, i.e.…”
Section: In Situ Nexafs and Xps Of Vxoy/sba-15supporting
confidence: 77%
“…It was shown in previous studies that in the case of V-SBA-15 no significant effects of vanadium loading on the structure of vanadium sites was observed for low vanadium loadings (<2.3 V nm -2 ). 24 In the case of the V-SBA-15 sample a higher reaction temperature was applied in order to reach comparable degrees of propane conversion at concurrent homogeneity of the catalyst part. The differences in the selectivity-conversion behavior at equal reaction conditions have been discussed in detail before.…”
Section: Resultsmentioning
confidence: 99%
“…24,38 However, recent time-dependent XPS experiments, which eliminate the influence of vacuum/X-ray radiation by extrapolating the temporal changes to t ) 0, indicate the absence (contribution ∼1%) of vanadium(III) in the case of dehydrated (hydrated) silica-supported vanadia samples. 24 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…multiple neighbouring reduced sites provide absorption sites for hydrocarbons, most likely unsaturated, causing coking and desorption hinderance for reaction intermediates [47]. Hess et al [58,59] observed an additional feature in their XPS of V x O y /SBA-15 samples, at even higher binding energy than expected for V…”
mentioning
confidence: 99%